If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 = 3(y + -4) + -7y Reorder the terms: -16 = 3(-4 + y) + -7y -16 = (-4 * 3 + y * 3) + -7y -16 = (-12 + 3y) + -7y Combine like terms: 3y + -7y = -4y -16 = -12 + -4y Solving -16 = -12 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. -16 + 4y = -12 + -4y + 4y Combine like terms: -4y + 4y = 0 -16 + 4y = -12 + 0 -16 + 4y = -12 Add '16' to each side of the equation. -16 + 16 + 4y = -12 + 16 Combine like terms: -16 + 16 = 0 0 + 4y = -12 + 16 4y = -12 + 16 Combine like terms: -12 + 16 = 4 4y = 4 Divide each side by '4'. y = 1 Simplifying y = 1
| 3(2q+5)=5(x+1q) | | x*x=-81 | | 4(2x-1)=2x+14 | | 10x+22=13x+10 | | 14x+14=36 | | 2x+5=8X+25 | | 4y+20-y-4=6 | | 5r^2+33r+40= | | 8(x-2)=40 | | 7-3x+9=5x | | -0.02x^2+1.4x-12=0 | | 6(b+5)+2=22+b | | x+10=43 | | -80000x+2000000=4200000 | | 13+8x=11-4 | | 5xn=400 | | -5(3+11n)=-10(10-3n) | | 11/2+12/6= | | -4x+10x=0 | | -80000x+2000000=3600000 | | 5(k-3)+6=-2k+12 | | ln(5)+ln(x-1)=0 | | 2/6+5/2= | | 7n-10=5n+2 | | -3x-11y=3 | | 5(2f+6)=5f-9 | | -4(1+p)=-8-2p | | 6x-12y=-6 | | 0=2x^2-25x+57 | | 8=18-5x | | 20x^2+12x-56=0 | | f(x)=3x^2+24x |